(untitled) (Altre Modernità, 2013)
The nineteenth-century Spanish American apocalyptic discourse ñ particularly the one developed after the military dictatorships of the 1970s and 1980s ñ is revealed as a language with a strong political connotation, providing alternatives to the dominant logic, and questioning hegemonic spaces of power. Apocalypse, in its double meaning of ìdestructionî of an ancient order and ìunveilingî of hidden truths, does not only characterize the themes of the contemporary literary production, but also its forms. Implying an ìapocalypticî discursive structure, the crisis thus becomes permanent. Starting from this premise, the essay takes into account some representative Spanish American literary works of the last three decades, paying special attention to Julio Cort·zarís short story ìApocalipsis en Solentiname,î and Jorge Volpiís novel El juego del Apocalipsis. In both texts, the apocalyptic ending is strictly related to the beginning: the incipit inexorably anticipates the conclusion in terms of both the apocalyptic theme and discourse. In Cort·zarís short story, apocalypse does not emerge in the course of the narration but it anticipates the (uncertain) interpretation of the ending, manifesting itself as a ìfantasyî strategy. In Volpiís novel, eschatology as the end of history appears throughout the narration as a pattern forging the charactersí fate. The apocalypse that is inborn in everyone of us (our dark side), is unveiled and represents the end of history.